Review of key factors controlling engineered nanoparticle transport in porous media - Wang, Mei; Gao, Bin; Tang, Deshan (Journal of hazardous materials, 2016)
[Display omitted] •Comprehensive overview of ENP transport in porous media.•Key factors of ENP transport are categorized into three groups.•Nature of ENPs affects their transport in porous media.•Nature of porous media affects ENP transport.•Nature of flow affects ENP transport in porous media. Nanotechnology, an emerging technology, has witnessed rapid development in production and application. Engineered nanomaterials revolutionize the industry due to their unique structure and superior performance. The release of engineered nanoparticles (ENPs) into the environment, however, may pose risks to the environment and public health. To advance current understanding of environmental behaviors of ENPs, this work provides an introductory overview of ENP fate and transport in porous media. It systematically reviews the key factors controlling their fate and transport in porous media. It first provides a brief overview of common ENPs in the environment and their sources. The key factors that govern ENP transport in porous media are then categorized into three groups: (1) nature of ENPs affecting their transport in porous media, (2) nature of porous media affecting ENP transport, and (3) nature of flow affecting ENP transport in porous media. In each group, findings in recent literature on the specific governing factors of ENP transport in porous media are discussed in details. Finally, this work concludes with remarks on the importance of ENP transport in porous media and directions for future research.